The Question of the Return of Weaving Machines from Turkey to Romania after World War I - Nurten Çetin (Yakın Dönem Türkiye Araştırmaları)
Romania, which has rich underground and surface resources, entered World War I on August 27, 1916, when it joined the Triple Entente States. It was defeated a short time later. The Alliance States took possession of some of the Romanian products and materials needed for their economy by seizing or purchasing them. During this period, some machines were bought by the Ottoman government, from places like the Altın Yıldız Company and Defterdar Mensucat Factory. When the war ended, Romania demanded the return of the machines. However, how to perform the action of returning them posed a problem for the Ottoman government. A Mixed Commission was established to deal with the issue, which brought to the foreground various economic, legal, and political issues. The problem was resolved on November 3, 1921 in a way that pleased the parties and did not disturb the relations between the two countries. Yet, even after returning the machines, some problems remained. This article examines Ottoman archive documents to shed light on the developments in the process of returning the machinery and equipment confiscated by the Ottoman government during the invasion of Romania in World War I.